PENGEMBANGAN VARIASI LATIHAN TEKNIK DASAR PENJAGA GAWANG DENGAN MENGGUNAKAN MEDIA BANTAL (BAN MENTAL) USIA 14-18 TAHUN DI SSB SELURUH KECAMATAN PAGAK KABUPATEN MALANG - Jadhug Bangun Saputra; Eko Hariyanto; Hariyoko Hariyoko (Jurnal Pendidikan Jasmani, 2015)
Abstract: Training in SSB SUMA no special coach to train the goalkeeper, the goal-keeper only to follow the training materials such as dribbling, passing, control. SSB SUMA until now there is no auxiliary media that support the specialized training the keeper. This research aims to develop a variety of exercises basic techniques goal-keeper using pillow media (mental tires), in order to exercise more varied goalkeeper in SSB SUMA. This study uses a model developed by Borg and Gall. Involving research subjects Football School students (SSB) throughout the District Pagak, the type of data that is generated in the form of quantitative and qualitative data. Get coaching from expert evaluation of the results of 89.58%, from football expert evaluation of the results obtained 88.75% of the media expert evaluation of the results obtained from the 39 items 6 and 32 very precise answer right answer and one answer is less precise means it can be concluded that the product This floating can be used as a media exercise. A small group of test results obtained 86.71%, so that it can be tested to the development of a large group, large group trial results obtained 88.47%, so that the product development of this research can be used as a medium for training and product development is expected to be used as reference trainers to improve the basic techniques of the keeper.Key words: training, goalkeeper, pillows (tire mental)ABSTRAK: Latihan di SSB SUMA belum ada pelatih khusus untuk melatih penjaga gawang, penjaga gawang hanya mengikuti materi latihan  seperti dribbling, passing, control. Di SSB SUMA sampai saat ini belum ada media bantu yang menunjang latihan khusus penjaga gawang. Penelitian ini bertujuan untuk mengembangkan variasi latihan  teknik dasar penjaga gawang dengan menggunakan media bantal (ban mental), agar latihan penjaga gawang lebih bervariasi di SSB SUMA. Penelitian ini menggunakan model yang dikembangkan oleh Borg and Gall. Subjek penelitian melibatkan siswa Sekolah Sepakbola (SSB) seluruh Kecamatan Pagak, jenis data yang dihasilkan berupa data kualitatif dan data kuantitatif. Dari evaluasi ahli kepelatihan mendapatkan hasil 89,58 %, dari evaluasi ahli sepakbola didapat hasil 88,75%, dari evaluasi ahli media diperoleh hasil dari 39 butir soal 6 menjawab sangat tepat dan 32 menjawab tepat dan 1 menjawab kurang tepat  berarti dapat disimpulkan bahwa produk pengambangan ini dapat dijadikan sebagai media latihan. Dari uji coba kelompok kecil diperoleh hasil 86,71%, sehingga pengembangan ini dapat diujicobakan ke kelompok besar, uji coba kelompok besar diperoleh hasil 88,47%, sehingga produk pengembangan penelitian ini dapat digunakan sebagai media latihan dan produk pengembangan ini diharapkan dapat dijadikan referensi pelatih untuk meningkatkan teknik dasar penjaga gawang. Kata Kunci: latihan, penjaga gawang, bantal (ban mental)